Open Science approaches at the University of Edinburgh - Donnelly, Martin (Septentrio Conference Series, 2018)
Watch the VIDEO. The University of Edinburgh is a large, research-intensive, civic university at the heart of Scotland’s capital. As a member of the League of European Research Universities (LERU), the Universitas 21 consortium and the Russell Group, we value and cultivate partnerships and collaborations as second nature, and seek to be recognised among the world’s top universities. These are interesting times for us, not least from Open (and data-driven) Science perspectives. In May 2018 the LERU Rectors Assembly assembled in Edinburgh, where they collectively endorsed LERU’s Roadmap for Open Science; a movement which requires considerable alterations to traditional researcher behaviours, and increasingly balancing intellectual investment and ownership of research with “the common good.” More recently, in August the UK Prime Minister and the Scottish First Minister met at the University to launch the Edinburgh and South East Scotland City Region Deal, a £1.3bn investment package designed to increase the contribution of research, data analytics expertise and graduate skills to the region’s economy, ultimately aiming to make Edinburgh “the data capital of Europe.” The timing of these developments provides a challenge, however, as Edinburgh, Scotland and the rest of the UK prepare to leave the European Union in the Spring of 2019. In an ideal world Science and Scholarship would be independent of political shifts, focused as they are on ideals of universal truth, but the means via which research is funded, performed and disseminated are necessarily grounded in political reality. Edinburgh’s default responses to the changes and challenges we face are to influence them positively – or mitigate them proactively – wherever we can, and to prepare ourselves for their impact where we cannot do otherwise. The University’s newly integrated Research Data Support (RDS) team is a cornerstone of our institutional Digital Research Services. We aim to provide holistic, responsive, tailored and researcher-focused support to the University community, helping collectively meet contemporary expectations in scholarly communications, including Open Science requirements to make data (and code) available alongside publications to enable their conclusions to be reproduced. The RDS has published a Roadmap for ongoing development, and alongside other infrastructural and support units such as the Scholarly Communications and Research Information Systems functions – and together with the externally focused infrastructure, advocacy and skills development centres that Edinburgh hosts, such as the Digital Curation Centre and the Software Sustainability Institute – we are a key component of the University’s broader Open Science strategy. In this presentation we will describe and discuss Edinburgh’s Open Science environment and approaches, within the broader landscape of changing expectations, political risks and scientific and societal opportunities. We will discuss the benefits and challenges of Open approaches within and beyond the Sciences, and the challenges involved in turning the European Commission’s “as open as possible, as closed as necessary” dictum into reality, including outreach and skills development activities. Finally we will look at the University’s current RDS Roadmap, and consider how this might develop and adapt in the exciting (and potentially turbulent) years ahead.